Productivity differences between organic and other vegetable farming systems in northern Thailand - Pranthanthip Kramol (2018)
Copyright © 2013 Cambridge University Press. We analyzed the productivity levels of smallholder farms in northern Thailand practicing different 'clean and safe' vegetable farming systems or conventional vegetable (CV) production. 'Clean and safe' farmers are categorized into three groups based on their use of synthetic chemicals: organic, pesticide-free and safe-use. Farm-level data on vegetable production were collected from random samples of farms operating these farming systems. A standard stochastic production frontier model and a metafrontier model were estimated for each system to obtain estimates of technical efficiency (TE) with respect to their cohorts, metatechnology ratios (MTRs, showing the extent of technology gaps between farming systems) and overall productivity measures. Productivity levels were found to vary moderately between farming systems. 'Clean and safe' farms achieved a higher mean TE score than conventional farms, indicating a more efficient use of inputs in producing a certain level of output within their system. However, their MTRs were significantly lower than those of conventional farmers, indicating greater production technology constraints because of the need to conform to strict guidelines. All four farming systems had at least one farmer who could overcome the technological constraints to achieve the highest possible output regardless of the technology used. Effective assistance providers were found to be crucial for farmers to achieve high productivity in the organic farming system. Improvements are needed to raise low productivity levels through technology transfer, value chain improvement and farmer capacity in production and marketing. The required improvement strategies differ among farming systems.